THE INFLUENCE OF PERSONAL ENGINEERING CAPABILITIES, EDUCATION AND TRAINING, AND THE ADVANCE OF INFORMATION TECHNOLOGY ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS (Case Study on MSMEs in Yogyakarta) - Teguh Erawati; Sri Ayem; Ronald Ario Tahu (Universitas Muhammadiyah Makassar, 2022)
This study aims to explain personal technical skills, education and training, as well as the sophistication of information technology on accounting information systems. In this study, research uses a quantitative approach because the analysis is based on existing theories and is related to the research topic. The theory used by researchers is the theory of personal engineering skills, education and training, information technology sophistication. The sample used was 51 people who were determined by the saturated sample method. The data technique used was a questionnaire. The analysis technique used is multiple linear regression with a significant level of 0.05. The results showed that (1) the variable, personal engineering skills had a positive and significant effect on the accounting information system (2) Education and training had a positive and significant impact on the accounting information system (3) the sophistication of information technology had a positive and significant effect on the accounting information system. Companies should pay attention to the skills of personal engineering, education and training, as well as the sophistication of information technology to improve accounting information systems (4) the ability of personal engineering, education and training, as well as sophisticated technology simultaneously to accounting information systems